2018
DOI: 10.11604/pamj.2018.31.23.15153
|View full text |Cite
|
Sign up to set email alerts
|

Applicability and outcome of laparoscopic adrenalectomy for large tumours

Abstract: Laparoscopic adrenalectomy has been shown to be as safe and effective as conventional open surgery for small and benign adrenal lesions. With increasing experience with laparoscopic adrenalectomy, this approach has become the procedure of choice for the majority of patients requiring adrenalectomy. In our department, from 2011 to 2016, a total of 28 patients with 31 adrenal tumours underwent laparoscopic adrenalectomy regardless of tumour size. Our policy in the department is to exclude adrenal tumours that ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…15,[21][22][23][24] Previous reports suggested that the cutoff for performing a minimal invasive approach is <6 cm due to the increased risk of malignancy. 4,13,[25][26][27] More recent reports on the feasibility and safety of performing larger size masses up to 12 cm, [27][28][29][30][31] especially in the era of robotic surgery, with growing evidence to support its safety. 27,32,33 Unfortunately, the tumor size is not available through the VASQIP data, which represents a limitation of this study, and may lead to selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…15,[21][22][23][24] Previous reports suggested that the cutoff for performing a minimal invasive approach is <6 cm due to the increased risk of malignancy. 4,13,[25][26][27] More recent reports on the feasibility and safety of performing larger size masses up to 12 cm, [27][28][29][30][31] especially in the era of robotic surgery, with growing evidence to support its safety. 27,32,33 Unfortunately, the tumor size is not available through the VASQIP data, which represents a limitation of this study, and may lead to selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…In their retrospective analysis, Mohammed et al proved that there is no priority of the open approach in adrenal tumors that are 5 cm or larger concerning complication rate, length of stay, mortality, or oncologic outcomes. Accordingly, they recommended laparoscopic adrenalectomy for all adrenal tumors regardless of their size [15]. Robotic-assisted resection was also recommended in more difficult cases or larger tumors, as it may provide the needed dexterity for handling such tumors [16].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, rigth-sided, large-sized or hormonal active tumors are believed to be more challenging but some recent publications claim otherwise. [6,10,11] More interestingly, Limberg et al [12] reported that laparoscopic adrenalectomy is as safe and feasible as laparoscopic cholecystectomy procedure and emphasized that physicians should not hesitate to refer their patients to surgery. Herewith, on the basis of our experience in minimally invasive surgery, we aimed to demonstrate the applicability of the procedure by representing our 5-year results.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Although many studies comparing transabdominal and retroperitoneal approaches have shown different advantages, transabdominal approach is mostly preferred because it provides a large area in the abdomen, allows excision of medium size (<6 cm) masses and is easy to teach [1,3] but there is still a debate about laparoscopic approach for large (>6 cm) or malignant masses. [4][5][6] The laparoscopic approach to adrenal masses has now become the standard procedure, and with the widespread use of laparoscopy, its use has increased rapidly. However, it is emphasized that it should still be performed in experienced centers because of its surgical risks.…”
Section: Introductionmentioning
confidence: 99%